Heart-lung transplantation for cystic fibrosis. 2: Outcome. Issue 9 (September 1991) - Whitehead, B; Helms, P; Goodwin, M; Martin, I; Scott, J P; Smyth, R L; Higenbottam, T W; Wallwork, J; Elliott, M; de Leval, M
Abstract : From March 1988 to March 1990, 11 children with cystic fibrosis (age 5-15 years) underwent combined heart-lung transplantation at our institutes. Maintenance immunosuppression consisted of cyclosporin and azathioprine with corticosteroids and antithymocyte globulin used perioperatively and during rejection episodes. Six patients (55%) survive from 1.5-23 months all of whom have improved life quality. Actuarial survival to 1 year was 55%. At six months after transplant, mean forced expiratory volume at one second was 73.5% of predicted normal, compared with 25% before transplant. There was one perioperative death, three later deaths associated with obliterative bronchiolitis at two, eight, and nine months, and one from mediastinitis at four months. Of the 15 children accepted for transplantation but not receiving grafts, 10 have died (eight within four months of being placed onto the transplant list). Early postoperative problems included acute reversible rejection (n = 10), meconium ileus equivalent (n = 3), and pancreatitis (n = 1). There was a high incidence of later pulmonary rejection with a mean of 5.7 episodes per patient in the first six months. Pulmonary infection occurred relatively infrequently, with Pseudomonas aeruginosa being the most common pathogen. Persistent diabetes mellitus requiring insulin occurred in four and systemic hypertension developed in one.